Kualitas Layanan Kereta Commuter Indonesia: Customer Satisfaction Index - abdul muis; Dila Novita (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2020)
Increasingly developing technology, The Indonesian Commuter Train Company is required to maintain and improve services. This is a step that must be taken as the only provider of rail services in Jakarta, Bogor, Depok, Tangerang, and Bekasi areas. With the increasing number of choices of types of urban transportation services provided to the community, efforts to continue to make service improvements are imperative. This study analyzes the quality of service provided by The Indonesian Commuter Train Company at Cikarang Station from the passengers perspective. This research applies quantitative methods with survey data collection techniques through questionnaires. The population chosen was the commuter train service users at Cikarang Station with a sample of 100 respondents. The sampling technique used Simple Random Sampling. This study applies five SERVQUAL indicators. Data analysis was performed descriptively, Importance Performance Analysis, and Customer Satisfaction Index. The results of the study show that the service at Cikarang Station is already